2018
DOI: 10.1111/odi.12917
|View full text |Cite
|
Sign up to set email alerts
|

IL‐6, TNF–α levels and periodontal status changes during the menstrual cycle

Abstract: Periodontal tissues did not exhibit evident changes, but this study demonstrated that the menstrual cycle affected the periodontium and induced inflammatory situations during the menstrual cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…There were no female participants in the study. Studies have shown that hormonal fluctuations during menstruation are associated with an increased expression of destructive inflammatory cytokines including IL-1 β 34 . Influence of hormonal fluctuations was minimized in this study.…”
Section: Discussionmentioning
confidence: 99%